DOI: 10.14264/uql.2018.860
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation of sources of water across multiple tropical rainforest trees

Abstract: Tropical forest water use is important for maintaining ecosystem function, tree productivity, growth, survival and nutrient cycling. However, explaining such use is complex in the field. Water stable isotope tracing of plant water use can shed light on such plant water sources but to date, species numbers tested at any given site across the globe have been minimal. Additionally, past tree water source studies were mostly based on methods using single isotopes of either (δD or δ 18 O) at a coarse spatiotemporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
2

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 81 publications
(110 reference statements)
2
3
2
Order By: Relevance
“…Predominant shallow water use was also observed in other studies for several evergreen species in seasonally dry tropical forests on fine textured soils (Goldsmith et al, 2012; Liu et al, 2010) and in a tropical forest with sandy soils (Sohel, 2018). However, uptake of deeper soil water occurs occasionally in seasonal tropical climates as well (Liu et al, 2010 reported >60 cm; Meinzer et al, 1999 reported >100 cm; Schwendenmann et al, 2015 reported >30 cm; Stahl et al, 2013 reported 100–120 cm).…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Predominant shallow water use was also observed in other studies for several evergreen species in seasonally dry tropical forests on fine textured soils (Goldsmith et al, 2012; Liu et al, 2010) and in a tropical forest with sandy soils (Sohel, 2018). However, uptake of deeper soil water occurs occasionally in seasonal tropical climates as well (Liu et al, 2010 reported >60 cm; Meinzer et al, 1999 reported >100 cm; Schwendenmann et al, 2015 reported >30 cm; Stahl et al, 2013 reported 100–120 cm).…”
Section: Discussionsupporting
confidence: 74%
“…For instance, tree species or vegetation cover can affect soil water isotopic composition (Schwendenmann et al, 2015; Sprenger, Tetzlaff, & Soulsby, 2017) and roots or animal burrows can lead to preferential flow paths. Compared to a lateral soil water isotopic range of 10.7‰ δ 18 O in a 1 ha temperate forest (Goldsmith et al, 2018), our lateral range of up to 6‰ δ 18 O was lower, but twice as high as in seemingly homogeneous soils in an Australian tropical forest (Sohel, 2018). Unlike Goldsmith et al (2018) and Sohel (2018), who only sampled once, we sampled four times.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…An increased study of woody plant water sources will help in identifying complementarities among tree species, which can then inform the design and management of mixed-species plantations. Even though we considered article until 2014, there are some researches [56][57][58][59][60][61] published after 2014. In most cases, those research themes matched with our proposed research themes.…”
Section: Concluding Remarks and Recommendationsmentioning
confidence: 99%